PROTEKSI HAK CIPTA ATAS KONTEN TIKTOK YANG DISIARKAN PADA ACARA TELEVISI - Fenti Dwi Sugiati; Mas Anienda Tien F (LPPM Universitas Ekasakti Padang, 2023)
According to Law Number 28 of 2014 Concerning Copyright, Tiktok content is a work that is protected by copyright. However, TikTok content belonging to copyright holders is still being violated. The purpose of this research is to explore the laws relating to copyright infringement of TikTok content that is played back on television programs and to assess the obligations of television stations to comply with the Copyright Act. This research is looking for a suitable legal solution that can be used. With a statutory descriptive and analytic approach, this study uses a normative legal research methodology. The results show that copyright infringement occurs when TikTok content is shown on television for commercial purposes because it violates the economic rights of the creator. Content creators can take preventive legal actions to protect their rights, such as signing agreements.